Epigenetic regulation in adult neural stem cells - Shi, Jiajia; Wang, Zilin; Wang, Zhijun; Shao, Guofeng; Li, Xiajun (Frontiers in Cell and Developmental Biology, 2024)
Neural stem cells (NSCs) exhibit self-renewing and multipotential properties. Adult NSCs are located in two neurogenic regions of adult brain: the ventricularsubventricular zone (V-SVZ) of the lateral ventricle and the subgranular zone (SGZ) of the dentate gyrus (DG) in the hippocampus. Maintenance and differentiation of adult NSCs are regulated by both intrinsic and extrinsic signals that may be integrated through expression of some key factors in the adult NSCs. A number of transcription factors have been shown to play essential roles in transcriptional regulation of NSC cell fate transitions in the adult brain. Epigenetic regulators have also emerged as key players in regulation of NSCs, neural progenitor cells and their differentiated progeny via epigenetic modifications including DNA methylation, histone modifications, chromatin remodeling and RNA-mediated transcriptional regulation. This minireview is primarily focused on epigenetic regulations of adult NSCs during adult neurogenesis, in conjunction with transcriptional regulation in these processes.